Pengaruh Peer Group Support Dalam Pelaksanaan Therapeutic Community Terhadap Peningkatan Motivasi Residen Untuk Menjalani Rehabilitasi - Rahayu Tri Nuritasari; Septi Viantri Kurdaningsih; M. Ramadhani Firmansyah (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2022)
Objective: The purpose of this study was to determine the effect of peer group support in therapeutic community to motivation resident for rehabilitationMethods: The research uses quantitative methods. This type of research is pre-experimental design with one group pretest-posttest. Sampling technique using total sampling with the number of respondents 80 residence. Data collecting technique in this study is to distribute questionnares to respondents. The analysis technique in this study uses Wilcoxon signed rank test.Results: The results of pre-test study 57,5% had low motivation and 27,5% had a moderate motivation, and after getting the intervention in getting resident who has a high motivation to increase to 70%. Conclusion: Peer group support in the implementation of the therapeutic community resident have a significant effect on motivation for rehabilitation.